Efficient Separation of Organic Dyes using Polyvinylidene Fluoride/Polyethylene Glycol-Tin Oxide (PVDF/PEG-SnO2) Nanoparticles Ultrafiltration Membrane - Saleem, Abdullah Ghanim; Al-Jubouri, Sama Mohammed (Applied Science and Engineering Progress, 2024)
This work studies developing ultrafiltration (UF) membranes using organic and inorganic additives to remove organic dyes at UF conditions with high effectiveness. Flat sheet (18 wt%) polyvinylidene fluoride (PVDF) membranes were prepared via phase inversion and then developed by adding 6 wt% polyethylene glycol (PEG) as a pore former. Furthermore, the PVDF/PEG membranes were developed by embedding tin oxide nanoparticles (SnO2 NPs) with different contents of 0.3, 0.6, and 0.9 wt%. The prepared membranes were examined for their performance in the dye removal before being characterized using the field emission scanning electron microscope, atomic force microscopy, contact angle, Fourier-transform infrared spectroscopy, surface charge, porosity, mean pore size, tensile strength, and elongation at break. The performance was tested regarding pure water flux (PWF), permeate flux, and dye removal (R%). The effect of dye concentration and pH of the feed solution on the permeate flux and R% was also investigated. In addition, the antifouling features in terms of flux recovery ratio, reversible fouling, irreversible fouling, total fouling, and the R% were studied using the PVDF/PEG membrane and the membrane containing 0.3 wt% of SnO2 NPs. The contact angle decreased from 78.85° to 51.88°, and the PWF rose from 7.16 to 135.71 L/m2.h for PVDF and PVDF/PEG-SnO2 (0.3 wt%) membranes, respectively. The R% of rhodamine B (RhB) slightly decreased from 93.08 to 91.26, and 87.71% for PVDF, PVDF/PEG, and PVDF/PEG-SnO2 (0.3 wt%) membranes, respectively. Then, it increased with increasing NPs concentration up to 90.17 and 92.23% for PVDF/PEG-SnO2 (0.6 wt%) and PVDF/PEG-SnO2 (0.9 wt%) membranes, respectively. Also, the molecular weight cutoff was calculated using RhB as a cationic dye, acid orange 10, and congo red as an anionic dye and it was 520 Da.